Individual'naya otsenochnaya shkala kak faktor minimizatsii neeffektivnykh fizicheskikh nagruzok i psikhicheskikh sostoyanii u lyzhnits v usloviyakh nizkogor'ya - Sivakov, V. I. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The aim of this paper was to define the influence of frustration on the female skiers during sports training in the conditions of highlands. The research examines the influence of the physical loads on the psychophysical state of female skiers in the conditions of highlands. The definition of influence of physical loading on frustration in female skiers during acclimatization and reacclimatization was represented in the research also. The huge physical loads in the acclimatization period reduce the working capacity, worsen the state of health, the special preparedness and raise the condition of frustration. It confirms the not optimum mode of physical loading of female skiers in the conditions of highlands. Female skiers feel the high frustration at the acclimatization period and the low frustration at the reacclimatization period. The account of the psychophysical state in the period of training will promote the rational application of physical loading and the management of the mental state of female skiers.